Defining tropism and activity of natural and engineered extracellular vesicles - Choi, Wooil; Park, Dong Jun; Eliceiri, Brian P. (Frontiers in Immunology, 2024)
Extracellular vesicles (EVs) have important roles as mediators of cell-to-cell communication, with physiological functions demonstrated in various in vivo models. Despite advances in our understanding of the biological function of EVs and their potential for use as therapeutics, there are limitations to the clinical approaches for which EVs would be effective. A primary determinant of the biodistribution of EVs is the profile of proteins and other factors on the surface of EVs that define the tropism of EVs in vivo. For example, proteins displayed on the surface of EVs can vary in composition by cell source of the EVs and the microenvironment into which EVs are delivered. In addition, interactions between EVs and recipient cells that determine uptake and endosomal escape in recipient cells affect overall systemic biodistribution. In this review, we discuss the contribution of the EV donor cell and the role of the microenvironment in determining EV tropism, and thereby determining the uptake and biological activity of EVs.